Managing cooperation, coordination, and legitimacy: Control of contracted public services. Issue 6 (15th August 2016) - Johansson, Tobias; Siverbo, Sven; Camén, Carolina
Abstract : Purpose: – The purpose of this paper is to create knowledge about what factors explain the design of control systems for contracted public services. Design/methodology/approach: – Questionnaire data analyzed with structural equation models. Findings: – Legitimacy-seeking is the most important driver in explaining intensity in control of contracted public services. Competition increases the intensity of control which is opposite to standard transaction cost reasoning. Coordination requirements do not affect the design of control systems for contracted public services. Research limitations/implications: – The study suffers from limitations in the form of the use of perception and questionnaire data and imposes restrictions on empirical generalization. Practical implications: – Supplier competition may add control costs rather than lower them. The strong focus on stakeholder alignment may induce more intensive control than necessary for supplier alignment. Originality/value: – The authors add important knowledge on the determinants of control system design for contracted public sector services. The authors conceptualize and measure the control system in use in a more compelling manner than previous research.